Association of Serum Level of Substance P with Glycemic Control Indices and Lipids Profile in Non-Obese Type 2 Diabetic Patients - Shahad W. Ahmed; Hussein Ali, Shatha (Iraqi Journal of Pharmaceutical Sciences, 2025)
Hyperglycemia and hyperinsulinemia, two common metabolic disorders associated with type 2 diabetes mellitus, are the main causes of metabolic abnormalities that result in a wide range of complications, such as cardiac dysfunction, nephropathy, neuropathy, and retinopathy. Substance-P is an 11-amino acid neuropeptide that is highly conserved and secreted by sensory nerve endings as well as different types of non-neural cells. It was believed that substance P would reduce inflammation triggered on by diabetes, interrupting the development of complications associated with this disease. The current study aims to investigate whether serum levels of substance P are associated with glycemic measures &/or lipids profile in patients with type 2 diabetes mellitus who are not obese. A case-control study involved eighty-five adult subjects (46 males&39females), aged (30-60) years, and was divided into two groups; Group-1: 53 non-obese type 2 diabetic patients (BMI range:18.6-29.9 kg/m2), were selected from the out-patient clinic of The National Centre of Diabetes Treatment & Research, Group-2: 32 individuals were chosen at random from the population as a whole to serve as control Healthy subjects; their ages and sexes were matched to those of the patients. The fasting serum glucose, insulin, homeostatic model assessment-insulin resistance (HOMA-IR), total cholesterol, triglycerides, and haemoglobin A1c (HbA1c) values exhibited significantly higher values in diabetic patients in comparison to controls. (p-value =0.001). Whereas, the serum levels of substance P and high-density lipoprotein were markedly lowered in diabetic individuals relative to the control group. (p-value =0.001). Serum substance P displayed no significant correlations with the studied variables (P˃0.05). In conclusion, serum levels of substance P were lowered significantly in type 2 non-obese diabetic patients compared to healthy controls and displayed non-significant correlations with studied glycemic indices nor with lipids profile.